Adapted physical exercise enhances activation and differentiation potential of satellite cells in the skeletal muscle of old mice. Issue 5 (6th January 2016) - Cisterna, Barbara; Giagnacovo, Marzia; Costanzo, Manuela; Fattoretti, Patrizia; Zancanaro, Carlo; Pellicciari, Carlo; Malatesta, Manuela
Abstract: During ageing, a progressive loss of skeletal muscle mass and a decrease in muscle strength and endurance take place, in the condition termed sarcopenia. The mechanisms of sarcopenia are complex and still unclear; however, it is known that muscle atrophy is associated with a decline in the number and/or efficiency of satellite cells, the main contributors to muscle regeneration. Physical exercise proved beneficial in sarcopenia; however, knowledge of the effect of adapted physical exercise on the myogenic properties of satellite cells in aged muscles is limited. In this study the amount and activation state of satellite cells as well as their proliferation and differentiation potential were assessed in situ by morphology, morphometry and immunocytochemistry at light and transmission electron microscopy on 28‐month‐old mice submitted to adapted aerobic physical exercise on a treadmill. Sedentary age‐matched mice served as controls, and sedentary adult mice were used as a reference for an unperturbed control at an age when the capability of muscle regeneration is still high. The effect of physical exercise in aged muscles was further analysed by comparing the myogenic potential of satellite cells isolated from old running and old sedentary mice using an in vitro system that allows observation of the differentiation process under controlled experimental conditions. The results of this ex vivo and in vitro study demonstrated that adapted physical exercise increases the number and activation of satellite cells as well as their capability to differentiate into structurally and functionally correct myotubes (even though the age‐related impairment in myotube formation is not fully reversed): this evidence further supports adapted physical exercise as a powerful, non‐pharmacological approach to counteract sarcopenia and the age‐related deterioration of satellite cell capabilities even at very advanced age.